TBL: Genetic Testing and Personalized Medicine - Matthew Smolkin; Sharon Wenger (Association of American Medical Colleges, 2014)
Abstract Introduction Personalized medicine represents the transition of advances in genomic research/discovery into clinical practice. It is a field that is exponentially increasing in application and scope. The purpose of this team-based learning (TBL) module is to discuss the basic application of genetic testing to personalized medicine for treatment of diseases with second-year medical students. Methods The module progresses like most TBL modules, in which the learners complete a preassigned reading before the session, progress through an individual readiness assurance test (IRAT), group readiness assurance test (GRAT), applications questions, and a group report-out. Results In the first year that this TBL was implemented the students scored a 57% average on the IRAT and on the GRAT the score improved to an average score of 83%. The second year with five questions, the IRAT average was 81% with a 92% for the GRAT. The overall average class score on the application exercise was 92%. Discussion We believe the improvement in scores over the past year was related to reduction and modification of the format of the IRAT/GRAT and/or application questions. Additionally, as more TBL modules have been introduced to the medical school curriculum, students and faculty have become accustomed to this style of teaching and are more aware of their responsibilities and expectations.